A Code of Conduct for Members of Parliament? - Finlayson, Christopher F (Victoria University of Wellington Law Review, 1998)
The integrity of a government is largely judged by the conduct of its members. In recent times, it could be argued, that this has been wanting. The author argues tlhat this is in part due to the lack of clarity in the rules of conduct applying to members of Parliament, and the lack of sanctions (and corresponding lack of adherence) to those rules which do exist. After examining the approach taken by the Ontario, Canadian and United Kingdom legislatures, a statutory code of conduct based on the Ontario model is advocated for New Zealand.